ChemInform Abstract: Scalable, Easy Synthesis, and Efficient Isolation of Arylnitromethanes: A Revival of the Victor Meyer Reaction. Issue 25 (June 2016) - Alaime, Thibaud; Delots, Audrey; Pasquinet, Eric; Suzenet, Franck; Guillaumet, Gerald
Abstract: Reaction of benzyl‐type halides with AgNO2 allows the moderately efficient synthesis of arylnitromethanes.